2013
DOI: 10.1007/s40145-013-0077-6
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion behavior of Ti3AlC2 in molten KOH at 700 °C

Abstract: This paper investigated the corrosion behaviors of Ti 3 AlC 2 at 700 ℃ in molten KOH with various mass ratios. If the mass ratio of KOH:Ti 3 AlC 2 ≤2, Ti 3 AlC 2 can resist KOH hot corrosion in 2 h. Ti 3 AlC 2 suffered serious corrosion attack if the mass ratio≥3. The main compositions of corroded samples were amorphous graphite and potassium titanates (K 2 O·nTiO 2 ). If the samples were washed by acid and dried, potassium titanates could decompose to K 2 O and amorphous rutile. Based on the experimental resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…is also confirmed that s en Al [25][26][27], Si atoms migrate outward, leav It Ti 3 AlC 2 decomposes at 1450 in vacuum ℃ by the outward diffusion of Al atoms and can be corroded in molten KOH at 700 ℃ [28,29]. This work reveals another manner of decomposition of an MAX phase, by ball milling.…”
Section: Reaction Mechanism For Formation Of Ti 2 Pbcsupporting
confidence: 66%
“…is also confirmed that s en Al [25][26][27], Si atoms migrate outward, leav It Ti 3 AlC 2 decomposes at 1450 in vacuum ℃ by the outward diffusion of Al atoms and can be corroded in molten KOH at 700 ℃ [28,29]. This work reveals another manner of decomposition of an MAX phase, by ball milling.…”
Section: Reaction Mechanism For Formation Of Ti 2 Pbcsupporting
confidence: 66%
“…MAX phases, the precursors of MXenes, are ternary carbides or nitrides with the general formula of M n+1 AX n , where M is an early transition metal; A is an A-group element (mostly group IIIA or IVA); X is either carbon or nitrogen and the value of n can be 1, 2, or 3 [17][18][19][20]. A typical MAX compound consists of metallic A layers and ceramic M n+1 X n layers.…”
Section: Introductionmentioning
confidence: 99%
“…In the samples treated at 275 and 350 °C the D and G bands at 1350 and 1575 cm −1 (characteristic for graphitic layers) are absent. The sample treated at 350 °C shows two faint signals at 781 and 868 cm −1 that correspond to titanate structures [27] . This, combined with the absence of any TASC signals and/or other sharp signals in XRD (Figure S1, top curve), implies that most of the TASC has converted into amorphous titanate(s).…”
Section: Resultsmentioning
confidence: 93%
“…Recently, less hazardous delamination methods were developed using alkaline treatment [24] . The literature describes a variety of treatments, ranging from low NaOH concentrations all the way to molten NaOH [25–28] . Such etching dissolves the aluminium between the titanium carbide layers, causing delamination.…”
Section: Introductionmentioning
confidence: 99%